Effect of Drying on Extraction of Anthocyanins from Syzygium cumini (Jamun) - Kaur, Amritpreet (My University, 2023)
Syzygium cumini, commonly known as jambolana or Indian blackberry, is a fruit rich in anthocyanins with significant health-promoting properties. This study used conventional solvent extraction (using methanol as solvent) to compare the anthocyanin recovery from different parts of Syzygium cumini, namely its pulp, pomace, and juice. The anthocyanin content was quantified using the pH differential method, which allowed for rapid and accurate estimation of anthocyanin concentration. Additionally, the drying effects on the fruit were investigated using three different foam mat drying methods: microwave foam mat drying, hot air oven foam mat drying, and vacuum foam mat drying. Regarding the drying effects, foam mat drying was employed at three different temperatures (50°C, 70°C, and 100°C) and power levels (180W, 360W, and 540W). The drying kinetics were studied and characterized using graphical analysis. Foam properties were assessed in terms of stability, density, expansion, and moisture content. The drying method that demonstrated the most favourable results in terms of temperature or power was selected for subsequent characterization. The selected drying method was further characterized through various analyses, including total extract yield, total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, ferric reducing antioxidant power (FRAP) assay, and antimicrobial tests.
Keywords: Syzygium cumini; Anthocyanins; Dehydration; Moistre content; Drying Kinetics